Outdoor activity time and depression risk among adults aged 40 years and older: a cross-sectional analysis of NHANES 2011–2018 data - Liu, Kai; Guo, Cheng; Xie, Juan; Cheng, Liming (Frontiers in Psychology, 2025)
BackgroundDepression is a significant global public health issue, affecting millions worldwide. Outdoor activities have shown potential mental health benefits, but the specific mechanisms and influencing factors remain unclear.ObjectivesThis study aimed to investigate the association between time spent outdoors and depression risk among U.S. adults, with a focus on variations across age and ethnic groups.MethodsUsing data from the NHANES 2011–2018 survey, we analyzed 9,036 adults aged 20 years and older. Participants self-reported their outdoor activity time and depressive symptoms. Statistical analysis, accounting for various demographic and lifestyle factors, was employed to assess the relationship between outdoor activity and depression risk.ResultsSpending more time outdoors was associated with a 51% lower risk of depression (odds ratio: 0.51, 95% CI: 0.40–0.64). Subgroup analysis revealed that this association was particularly pronounced among adults aged 40 and older, as well as non-Hispanic whites and non-Hispanic blacks.ConclusionEncouraging outdoor activities may represent an effective public health strategy to reduce depression risk, particularly among middle-aged and older adults and specific ethnic populations. Public health policies should prioritize initiatives that encourage outdoor engagement, and future research is needed to explore the underlying mechanisms and population-specific responses to outdoor activity.